The Growth of Bakau Kurap (Rhizophora stylosa Griff.) at Muara Mangrove Nursery, Teluk Naga, Tangerang PERTUMBUHAN BAKAU KURAP (Rhizopora stylosa) DI PERSEMAIAN MANGROVE DESA MUARA, KECAMATAN TELUK NAGA, TANGERANG - Omo Rusdiana; Andi Sukendro; Nizza Nadya Rachmani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Mangrove rehabilitation activities that are being undertaken in Muara village include seedling and planting activities for various species of mangroves, especially Rhizophora stylosa Griff. (bakau kurap). The villagers have problem to see the differences of ripe and mature fruit according to the activities. They often pick the ripe fruits that still have pieces of fruit although ripe fruits need preface treatment that take long time to be a seed. This study was conducted to obtain information about the development of bakau kurap growth in order to obtain a better cultivation technique based on propagules type at nursery, and the growth in the field based on planting treatments. Those are seedling in polybag, seedling non polybag, and direct seed from propagules. The result showed that during 4 months observation, direct seed from propagules treatment gave effect the highest of height growth about 3.19 cm/month. It suggested that rehabilitation activities should used direct seed from propagules at shallow area.Keywords: mangrove rehabilitation, Muara village, propagules, Rhizophora stylosa Griff.